Cold-Active Lipase from the Ice Cave Psychrobacter SC65A.3 Strain, a Promising Biocatalyst for Silybin Acylation - Victoria I. Paun; Sabina G. Ion; Giulia R. Gheorghita; Iunia Podolean; Madalina Tudorache; Cristina Purcarea (Molecules)
Cold-active lipase from the psychrophilic bacterial strain Psychrobacter SC65A.3 isolated from Scarisoara Ice Cave (Romania) was cloned and characterized as an extremophilic biocatalyst for silybin acylation. Structural analyses highlighted conserved motifs confirming a functional lipase and the presence of primary structure elements for catalysis at low temperatures. The recombinant enzyme (PSL2) heterologously expressed in Escherichia coli was purified in one step by affinity chromatography with a yield of 12.08 ± 1.72 µg L−1 of culture and a specific activity of 20.1 ± 3.2 U mg−1 at 25 °C. Functional characterization of PSL2 showed a neutral (7.2) optimal pH and a high thermal stability up to 90 °C. Also, this lipase was stable in the presence of different organic solvents, with 60% residual activity when using 20% DMSO. Kinetic measurements indicated performant catalytic efficiency of PSL2 for different short and long chain fatty acids, with Km in the mM range. The catalytic activity of PSL2 was assessed for silybin acylation with various fatty acids and fatty acid methyl esters, demonstrating a 90% silybin conversion when methyl decanoate ester was used. This result clearly highlights the biocatalytic capability of this new cold-active lipase.